A new approach for k(L)a determination by gassing-out method in pneumatic bioreactors - Cerri, Marcel Otavio [UNESP]; Esperanca, Mateus Nordi; Badino, Alberto Colli; Arruda Ribeiro, Marcelo Perencin de (Wiley-Blackwell, 2016)
BACKGROUND: Determination of the volumetric oxygen transfer coefficient (k(L)a) is very important for bioreactor design and process analysis. Among all the methods available, the gassing-out technique is one of the simplest and most widely used for this task. However, thismethod is very sensitive to the probe dynamics (due to delay effects), which can lead to inaccuracy in the k(L)a determination. This is especially pronounced for airlift bioreactors, where the circulation time affects the initial dynamics of the assay (a transient effect). In the presentwork, a newmethod for k(L)a determination is proposed. RESULTS: Values of k(L)a and the electrode response time (tau(e)) were determined experimentally, employing the traditional gassing-out method and the method proposed here. The latter was shown to be reliable, easier to apply, and suitable for the simultaneous determination of k(L)a and electrode sensitivity (k(e) = 1/tau(e)), without any need for additional assays. CONCLUSION: The new method overcomes the effects of probe delay on k(L)a determination, making the procedure faster and simpler. (C) 2016 Society of Chemical Industry
Keywords: oxygen transfer; gassing-out method; bioreactors; probe delay response; estimation of k(L)a